The relationship between working environment and employee’s productivity: a case study among employees in Sarawak Economic Development Corporation (SEDC) Kuching, Sarawak./ Shareena Azreen Hamdan - Hamdan, Shareena Azreen (2016)
This study was undertaken at the Sarawak Economic Development Corporation (SEDC), one of the public sectors located in Kuching, Sarawak. The purpose of the research was to determine the level of agreement on Employee’s Productivity affected by Working Environment in Sarawak Economic Development Corporation (SEDC) and to identify the relationship between the types of working environment (temperature, furniture and office layout) towards employee’s productivity. A total of 108 questionnaires were distributed among employees at SEDC, Kuching. The questionnaire was a structured questionnaire with a total number of 29 questions. Five questions were dedicated to demographic background, 6 questions were dedicated to temperature, 6 questions were dedicated to furniture, 6 questions were dedicated to office layout and 6 questions were dedicated to employees’ productivity. The data was analyzed using the SPSS Version 23. The results showed a positive relationship between the working environment (temperature, furniture, office layout) and employees’ productivity.